Robust and Secure Transmission Design for Reconfigurable Intelligent Surface Aided MU-SWIPT Systems With Hardware Impairments - Li, Yizhi; Zou, Yulong; Zhu, Jia; Ning, Boyu; Fang, He; Xu, Li; Ren, Zhichu; Lou, Yulei (IEEE transactions on vehicular technology, 2025)
In this paper, we investigate the robust and secure transmission for a reconfigurable intelligent surface (RIS) assisted multi-user simultaneous wireless information and power transfer (MU-SWIPT) system in the presence of an eavesdropper (Eve) with hardware impairments (HWIs). An optimization problem is formulated with the goal of maximizing the average sum secrecy rate (ASSR) of all users subject to the constraints of unit-modulus, maximum transmit power budget, and minimum average harvested power (AHP) threshold, taking into account the distortion noise caused by the HWIs at the base station (BS), users, and RIS. To handle this problem, the alternate optimization (AO) method is utilized to decouple the formulated problem into several sub-problems which are solved by optimizing one set of variables with other sets being fixed. Specifically, we employ the successive convex approximation (SCA) method to obtain the BS's transmit beamforming vectors (TBVs), while obtaining the RIS phase shifts based on the combination of SCA and penalty convex-concave procedure (CCP) algorithms, and an optimal power splitting (PS) ratio of each user is derived in a closed-form solution. Numerical results validate the effectiveness of the proposed AO and penalty CCP algorithms, and reveal the ASSR performance gain of the proposed RIS-assisted networks with robust transmission deign (Robust-RIS) scheme over the conventional schemes without considering HWIs or RIS.